2019
DOI: 10.1039/c8ra10233c
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition of atmospheric CO2to epoxides under solvent-free conditions: a straightforward route to carbonates by green chemistry metrics

Abstract: The conversion of CO2 into value-added organic compounds has received more attention over recent years since this gas is one of the major greenhouse gases, as well as an abundant, inexpensive, nontoxic, nonflammable and renewable one-carbon (C1) resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(17 citation statements)
references
References 93 publications
0
17
0
Order By: Relevance
“…[16] Considering environmental compatibility and the highefficiency catalytic conversion of CO 2 , there is the strong need to develop green catalysts capable of high conversions and selectivities, especially under solvent-free conditions. [17] The development of new catalysts for a so crucial reaction, able to work at mild process conditions with good performance, that are also reusable and easily separable, is therefore of high industrial interest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Considering environmental compatibility and the highefficiency catalytic conversion of CO 2 , there is the strong need to develop green catalysts capable of high conversions and selectivities, especially under solvent-free conditions. [17] The development of new catalysts for a so crucial reaction, able to work at mild process conditions with good performance, that are also reusable and easily separable, is therefore of high industrial interest.…”
Section: Introductionmentioning
confidence: 99%
“…Considering environmental compatibility and the high‐efficiency catalytic conversion of CO 2 , there is the strong need to develop green catalysts capable of high conversions and selectivities, especially under solvent‐free conditions [17] …”
Section: Introductionmentioning
confidence: 99%
“…Generally, catalysts are composed of a Lewis acid for the oxirane’s electrophilic activation and a Lewis base that acts as a nucleophile. Some of these catalysts are quaternary phosphate compounds, phosphine complexes, metal complexes, alkali metal halides, quaternary ammonium salts, and ionic liquids, among others [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Additionally, it has been observed that the catalytic activity increases when the acidity of the cation and the nucleophilicity of the halide increase [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since a number of advances and developments in the direct thioesterification of aldehydes have occurred from 1976 to present, a comprehensive review on this interesting research topic seems to be timely. In connection with our review articles on the formation of C-S bonds [11][12][13][14][15][16][17][18][19][20][21][22] and new methodologies in organic synthesis [23][24][25][26][27][28][29][30][31][32][33][34][35], in this Focus-Review, we will highlight recent progress on direct thioesterification of aldehydes with various thiol sources ( Figure 1), with special attention on the mechanistic aspects of the reactions. The cross-dehydrogenative coupling reactions of aldehydes with thiols are discussed first.…”
Section: Introductionmentioning
confidence: 99%